Laparoscopic limited liver resection decreases morbidity irrespective of the hepatic segment resected - Bueno, Alvaro (Blackwell Publishing Ltd, 2014)
OBJECTIVES: The laparoscopic approach is widely used in abdominal surgery. However, the benefits of laparoscopy in liver surgery have hitherto been insufficiently established. This study sought to investigate these benefits and, in particular, to establish whether or not the laparoscopic approach is beneficial in patients with lesions involving the posterosuperior segments of the liver. METHODS: Outcomes in a cohort of patients undergoing mostly minor hepatectomy (50 laparoscopic and 52 open surgery procedures) between January 2000 and December 2010 at the University Clinic of Navarra were analysed. The two groups displayed similar clinical characteristics. RESULTS: Patients submitted to laparoscopic liver resection (LLR) had a lower risk for complications [odds ratio (OR) = 0.24, 95% confidence interval (CI) 0.07–0.74; P = 0.013] and shorter hospital stay (OR = 0.08, 95% CI 0.02–0.27; P < 0.001) independently of the presence of classical risk factors for complications. In the cohort of patients with lesions involving posterosuperior liver segments (20 laparoscopic, 21 open procedures), LLR was associated with significantly fewer complications (OR = 0.16, 95% CI 0.04–0.71) and a lower risk for a long hospital stay (OR = 0.1, 95% CI 0.02–0.43). CONCLUSIONS: This study confirms that the laparoscopic approach to hepatic resection decreases the risk for post-surgical complications and lengthy hospitalization in patients undergoing minor liver resections. This beneficial effect is observed even in patients with lesions located in segments that require technically difficult resections.